(untitled) (Iraqi Journal of Medical Sciences, 2016)
It is believed that good ethical values flow out from one source, and follow a clear path that extends to every part of the world. These values honor the dignity of man as a human being honored by God almighty, and maintain man’s essential rights, including life, freedom, preservation of property, health and sufficiency, throughout man’s life. The Glorious Qura’n and Holy Shari`ah had contribute actively in regulation these ethical aspects in medicine. Although, these principles have been adopted in practice since the early days of Islamic culture and cited by many Muslims scientists. Nowadays, physicians are under prepared to deal with the new progress in medical technology like organ transplants, genetic engineering, and respirators that keep a person alive, only as a vegetable, for several years. Keywords: Ethics, Medical Ethics, Relgion, Islam, The Glorious Qura’n, Holy Shari`ah